Pembentukan Kader Anti Bullying pada Kelompok Anak Usia Sekolah di Kelurahan Pasie Nan Tigo, Kecamatan Koto Tangah, Kota Padang - Meri Neherta; Agus Sri Banowo; Ira Mulya sari; Arif Rohman Mansur; Deswita Deswita; Wedya Wahyu; Mutia Farlina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The phenomenon of bullying that often occurs in elementary school-age children is a severe problem that has an impact both physically and psychologically. Bullying in elementary school must be prevented immediately so that it does not become a habit that will be carried into adulthood. The purpose was to increase knowledge and assertive behaviour and the formation of anti-bullying cadres. The method used was health education and cadre training by providing a pretest and posttest. A knowledge questionnaire on bullying prevention was given to 60 elementary school students from 3 elementary schools in Pasie Nan Tigo Village, Lubuk Buaya Health Center, Koto Tangah District, Padang City. The results of this training found that students' average knowledge increased after being given health education. This training can increase students' knowledge and assertive behaviour about bullying prevention. Cadres are expected to prevent bullying in elementary school-age children so that life in the neighbourhood and school can run in peace and safety.